2011
DOI: 10.1002/marc.201000746
|View full text |Cite
|
Sign up to set email alerts
|

A Lipase‐Responsive Vehicle Using Amphipathic Polymer Synthesized with the Lipase as Catalyst

Abstract: We describe an enzyme-responsive polymeric vehicle, which is of great interest in controlled drug delivery, biosensing, and other related areas. The polymer synthesized using lipase as catalyst in DMSO has a favorable molecular structure that is quickly hydrolyzed by lipase in aqueous phase, and allows a fast release of encapsulated molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…To achieve these objectives, increased efforts in the fabrication of nanostructured drug delivery systems such as liposomes, 2 microspheres, 3 nanogels, 4 and polymeric micelles have been observed. 5,6 Kataoka and Harada 7 first reported that polyelectrolyte could reversibly form an assembly with proteins and DNAs through electrostatic interactions. Amphiphilic and neutral-ionic block co-polymers can also spontaneously form an assembly with counter-charged macromolecules in aqueous solution, forming a core-shell or core-corona structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve these objectives, increased efforts in the fabrication of nanostructured drug delivery systems such as liposomes, 2 microspheres, 3 nanogels, 4 and polymeric micelles have been observed. 5,6 Kataoka and Harada 7 first reported that polyelectrolyte could reversibly form an assembly with proteins and DNAs through electrostatic interactions. Amphiphilic and neutral-ionic block co-polymers can also spontaneously form an assembly with counter-charged macromolecules in aqueous solution, forming a core-shell or core-corona structure.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted release is also expected for a full display of the function of protein drugs. To achieve these objectives, increased efforts in the fabrication of nanostructured drug delivery systems such as liposomes, microspheres, nanogels, and polymeric micelles have been observed . Kataoka and Harada first reported that polyelectrolyte could reversibly form an assembly with proteins and DNAs through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution degree of dextran reached 23% and the enzyme nanogel had remarkable regioselectivity by discriminating between the three available secondary hydroxyl groups in the glucopyranoside unit. The product of hydrophobic group‐modified dextran could be used as a biocompatible, enzyme‐responsive material for preparing smart nanoparticles for drug delivery …”
Section: Possible Future Applications Of Protein‐incorporated Bionanomentioning
confidence: 99%
“…The polymer layer around individual enzyme molecules could be a) spatial polymer (e.g. inorganic/organic hybrid polymer [12][13][14][15][16][17][18] or acrylamide-bisacrylamide random copolymer [19]); (b) dendron [20]; (c) hyperbranched polymer [21]; or (d) smart or responsive polymer [22,23].…”
Section: Introductionmentioning
confidence: 99%